Transformasi Digital Layanan Publik: Studi Sosiologis Implementasi E-Litigasi dalam Perkara Perceraian di Pengadilan Agama Klaten - Yunus, Shalsya Malika; Riana, Ana (Journal of Social Movements, 2025)
This study investigates the implementation of e-litigation (e-litigasi) as a form of digital transformation in public legal services, focusing on divorce cases at the Klaten Religious Court, Indonesia. This research aims to explore whether the digital justice system can effectively promote inclusive and equitable access to justice for all societal segments, particularly in regions with limited digital literacy. A qualitative case study approach was employed, utilizing in-depth interviews, direct observation, and document analysis. The research subjects included judges, court staff, advocates, and litigants directly involved in e-litigation procedures. Data was analyzed to identify procedural dynamics, institutional readiness, social barriers, and user experiences. The findings indicate that while e-litigation enhances procedural efficiency and reduces the average litigation time from 42 to 24 working days, significant digital divides persist. Litigants with higher education and greater technological access tend to benefit more from the system, whereas those from rural or less-educated backgrounds face systemic exclusion. Institutional readiness also varies, with some court staff still lacking full digital proficiency, which affects the quality-of-service delivery. This study, although limited to a single location, highlights crucial implications for inclusive digital governance in the legal sector. To ensure an equitable transformation of public services, targeted digital literacy programs are recommended for vulnerable communities, along with a uniform enhancement of digital capacity among court human resources. Furthermore, the development of a digital justice framework that integrates social, institutional, and technological dimensions is essential to create a more responsive and equitable system.